Optimization simulation of fracturing parameters under different soft/hard coal + surrounding rocks in Yuwu Mine - Shaowei HAO; Jingshuo ZHANG; Ruijie CHEN; Yafei JING (Meikuang Anquan)
In order to improve the effectiveness of hydraulic fracturing, a numerical simulation software for hydraulic fracturing was used to address the issues of large differences in strength and poor compatibility between hydraulic fracturing parameters and different combinations of roof/ floor strata in 3# coal seam of Yuwu Mine. The fracture extension length, fracture width, flow conductivity of various combinations of coal and surrounding rock types (soft roof and hard coal, hard roof and soft coal, hard roof and hard coal) under different hydraulic fracturing parameters (perforating mode, construction displacement, total fluid volume, sand injection way, sand ratio, proppant particle size) were simulated, and based on this, the corresponding hydraulic fracturing pump injection parameters are optimized. The results indicate that when the combination is hard roof and soft coal, perforation and fracturing within a 2-4 m range of the roof is most effective, the pumping rate should be 8-10 m3/min, with an optimal average sand ratio of around 12%. For the combination of hard roof and hard coal, the pumping rate should be greater than 12 m3/min. A cyclic progressive sand-carrying fluid technique (using “pre-liquid - carrying sand liquid”) should be employed to increase the fracturing range and length of propped fractures; the total liquid volume is greater than 1 400 m3, and the average sand ratio of the first and second times is about 8% and 12%, respectively; for the combination of soft roof and hard coal, selective perforation and fracturing of certain coal layers in the roof and floor is recommended, with an optimal pumping rate of around 10 m3/min. In all three cases, the proppant is predominantly medium sand.